PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP PERLUASAN PANGSA PASAR PRODUK DANA TALANGAN HAJI DI BANK SYARIAH MANDIRI KCP UJUNGBERUNG DAN KCP RANCAEKEK BANDUNG - Nurrachmi, Intan (Jurnal Maps (Manajemen Perbankan Syariah), 2018)
This study departs from the hajj bailout financing facility which is a booming product because of the customer's interest, but in this case there is a difference in the target achievement between Bank Syariah Mandiri (BSM) Ujungberung KCP which is less successful in improving the hajj bailout products while the Rancaekek KCP is very superior in one consolidation Ahmad Yani Branch Office Bandung. This is what is interesting for researchers to carry out this research, the difference constraints include service quality and promotion factors. This phenomenon raises problems that must be examined, namely how the influence of service quality and promotion of market share expansion products hajj bailouts at Bank Syariah Mandiri KCP Ujungberung and KCP Rancaekek Bandung. This study aims academically to contribute in the study of Islamic economics in worksheets, especially the quality of service and promotion of market share expansion and practically expected to be able to provide input to all employees of BSM KCP Ujungberung regarding the quality of service and promotion of market expansion of bailout products. Hajj that has been successfully carried out by BSM KCP Rancaekek.The conclusion of this study is that there is a significant influence of service quality on the expansion of market share by 53.3% with a strong correlation of 0.730 and through t test, where t counts at 8.245 (> t table), then H_0 is rejected and H_i is accepted. Furthermore, there is a significant influence of promotion on the expansion of market share by 30.3% with a moderate / sufficient correlation of 0.550 through t test, where t counts is 4.219 (> t table), then H_ (0) is rejected and H_i is accepted. Then there is a significant influence of service quality and promotion simultaneously to the expansion of market share by 60.6% and a strong correlation of 0.784 and through Test F, where F count is 67.023 (> F table), then 〖H〗 _ ( 0) rejected and H_i accepted.